Psychological capital of employee and innovativeness of Small and Medium-Sized Enterprises (SMEs) - Salubre, Prince Lenard R.; Bahalla, Junalyn L.; Almagro, Ronald E. (Goodwood Publishing, 2024)
Purpose: This study explores the association between employees (PsyCap) and the innovation ability of Small and Medium-Sized Enterprises (SMEs). Research methodology: A descriptive correlational research design was employed, involving 150 respondents selected through simple random sampling. Two adapted questionnaires were used to measure PsyCap and innovation outcomes. Results: The results revealed A The strong positive relationship between employees' PsyCap and innovation outcomes (p<0.000, R=0.650), particularly creativity, risk-taking, and problem-solving. These findings underscore the importance of PsyCap as a significant predictor of innovative behavior within SMEs. Limitations: The study's limitations include its focus on SMEs, which may limit the generalizability of the results to larger organizations or different geographical regions. Despite this, the study contributes valuable insights into Human Resource Management (HRM) practices, emphasizing the need for targeted employee training and strategic organizational growth initiatives. Contributions: The findings highlight the critical role of Psychological Capital in fostering innovation and offer practical implications for enhancing competitiveness and sustainability in SMEs through the development of employees' psychological resources.